2017
DOI: 10.1111/mcn.12462
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic determinants of growth in a longitudinal study in Nepal

Abstract: Socioeconomic status (SES) is associated with childhood anthropometry, but little is known about how it is associated with tissue growth and body composition. To investigate this, we looked at components of SES at birth with growth in early and mid‐childhood, and body composition in a longitudinal study in Nepal. The exposure variables (material assets, land ownership, and maternal education) were quantified from questionnaire data before birth. Anthropometry data at birth, 2.5 and 8.5 years, were normalized u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…In this nationally representative study, US children aged 2–18 years old with higher HAZ tended to have a higher income and BMI percentile. This result is consistent with previous reports that HAZ was positively associated with household income [ 26 , 27 , 28 ] and BMI [ 29 ]. Although higher BMI was associated with greater HAZ in this study, without follow-up data we could not determine whether children with lower BMIs may eventually attain similar heights as their higher BMI peers.…”
Section: Discussionsupporting
confidence: 93%
“…In this nationally representative study, US children aged 2–18 years old with higher HAZ tended to have a higher income and BMI percentile. This result is consistent with previous reports that HAZ was positively associated with household income [ 26 , 27 , 28 ] and BMI [ 29 ]. Although higher BMI was associated with greater HAZ in this study, without follow-up data we could not determine whether children with lower BMIs may eventually attain similar heights as their higher BMI peers.…”
Section: Discussionsupporting
confidence: 93%
“…A study conducted in Ghana showed that as the number of food groups consumed by mother increased, so too did the number consumed by their children (Amugsi, Mittelmark, & Oduro, ). Low socio‐economic status has been identified as a risk factor for low child dietary diversity in a wide range of contexts (Karwa, Godhia, & Jadhav, ; Rakotonirainy et al, ) and associations with stunted growth are well‐established (Adekanmbi, Kayode, & Uthman, ; Devakumar et al, ; Leroy, Habicht, Gonzalez de Cossio, & Ruel, ; Poda, Hsu, & Chao, ). Similarly, land ownership was also an important protective factor for child feeding practices in this study and others (Devakumar et al, ; Hailemariam, Girmay, & Girmay, ), perhaps due to the central role of agriculture in ensuring food security via food provision and/or income.…”
Section: Discussionmentioning
confidence: 99%
“…Taking their results from a longitudinal study in Nepal, the authors observed that each increase in level of maternal education resulted in an increase in average height values of children and lower prevalence of stunting. Based on these findings, they suggested that maternal education would be the most influential socioeconomic determinant (Devakumar et al 2018).…”
Section: Parental Educationmentioning
confidence: 99%